A multi-stage planning model for transitioning to low-carbon integrated electric power and natural gas systems. (1st September 2022) - Wei, Zhinong; Yang, Li; Chen, Sheng; Ma, Zhoujun; Zang, Haixiang; Fei, Youdie
Abstract: The intensifying worldwide trend toward carbon neutrality necessitates an increasing penetration of renewable energy generation with increased short-term insecurity and operational flexibility requirements. However, current expansion planning methods for integrated electric power and natural gas systems fail to consider short-term uncertainties and to account adequately for the multi-stage retirement of coal-fired power generators and reduction in carbon-emission caps. The present work addresses these issues by proposing a multi-stage expansion planning model for integrated electric power and natural gas systems, which relies on natural gas as a clean energy source to provide the operational flexibility required to ensure integrated system security under load growth uncertainties and short-term uncertainties in wind power output. The application of non-anticipativity constraints guarantees that long-term uncertainties are realized in stages rather than in complete blocks. The effectiveness of the proposed model is verified by numerical results involving two integrated energy systems of different scales, where the installed capacity of renewables and gas-fired power accounts for 45.0% and 35.4% of the total installed capacity at the planning year, respectively. Highlights: We develop an expansion planning model of integrated power and natural gas systems. Short-term operating flexibility is considered at the planning stage. Multi-stage investment decisions made are independent of future uncertainties. Our model provides a transition solution towards low-carbon energy systems.